Thermal analysis of H.V. insulation oil during partial discharge detection - Gatea, Rasool Abdelfadil (2014)
Historically, the arc discharge analyzing technique was one of the first methods to determine the status of the insulation oil. Due to the harsh environment and the continue usage of the high voltage transformers, many problems of insulation can be produced leading to the failure of the transformer. The problem of the thesis is to find the best available solution to conduct real time analyzing of insulation oil of high voltage transformers, so that the high voltage transformer can be safeguarded from failure in the most effective and economic manner. In this work, the temperature of the insulation oil will be captured and calculated with and without partial discharge occurring. The simulated arc discharge is generated using 7.5 kV power source in two round shape steel electrodes having 5 mm gap. This distance (between the sensor and arc discharge source) is set at 5 cm. The infrared thermometer (laser gun) was used to capture the insulation oil temperature by sending a laser light toward the insulation oil and that light will be reflected beck and received by the device and then the temperature of the oil will be captured and measured. This study will help to predict the insulation oil age of high voltage transformers, which reduce the maintenance cost of high voltage transformer.